2015
DOI: 10.1016/j.celrep.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Co-evolution of Host and Pathogen: HCMV Downregulates the Prevalent Allele MICA∗008 to Escape Elimination by NK Cells

Abstract: Natural killer (NK) cells mediate innate immune responses against hazardous cells and are particularly important for the control of human cytomegalovirus (HCMV). NKG2D is a key NK activating receptor that recognizes a family of stress-induced ligands, including MICA, MICB, and ULBP1-6. Notably, most of these ligands are targeted by HCMV proteins and a miRNA to prevent the killing of infected cells by NK cells. A particular highly prevalent MICA allele, MICA008, is considered to be an HCMV-resistant "escape var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
123
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 32 publications
5
123
0
Order By: Relevance
“…We confirmed that assumption, as we showed the staining with an NKG2D fusion was reduced upon infection. Another, less likely, explanation is that because MICA is highly polymorphic and since it was shown that HCMV possesses different mechanisms for different alleles (37), it may be possible that HHV-6 cannot target the specific MICA alleles expressed by SupT1 and MOLT-3 cells. Additionally, it is possible that the reactions of a transformed T cell and primary T cells following viral sensing vary tremendously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that assumption, as we showed the staining with an NKG2D fusion was reduced upon infection. Another, less likely, explanation is that because MICA is highly polymorphic and since it was shown that HCMV possesses different mechanisms for different alleles (37), it may be possible that HHV-6 cannot target the specific MICA alleles expressed by SupT1 and MOLT-3 cells. Additionally, it is possible that the reactions of a transformed T cell and primary T cells following viral sensing vary tremendously.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells also possess numerous activating receptors that are able to recognize stressinduced self-ligands via the receptor NKG2D (31), immune regulatory self-molecules (for instance, the recognition of B7-H6 by the NKp30 receptor [32] or of CD48 by the 2B4 receptor [33]), or viral ligands such as the influenza virus-derived hemagglutinin that is recognized by both the NKp46 and NKp44 receptors (34,35). We and other groups have described several diverse viral mechanisms that manipulate cellular ligands for NK cells to escape the immune system (34,(36)(37)(38)(39)(40)(41)(42)(43)(44); however, knowledge about the interaction of HHV-6-infected cells with NK cells is currently missing.…”
mentioning
confidence: 99%
“…+ and DNAM-1 + cells (14)(15)(16)(17). In contrast, it is still debated whether and how HCMV upregulates NKG2DL, whereas for DNAM-1L it has not been investigated.…”
mentioning
confidence: 98%
“…NK cells are known mostly for their role in controlling viral infections (20,21) and have been shown to be involved in cytomegalovirus (CMV) (22)(23)(24), influenza virus (6,(25)(26)(27)(28), Newcastle disease virus (29), vaccinia virus (30), and human metapneumovirus (HMPV) infections (31,32). NK cells express a large repertoire of inhibitory receptors, which mostly recognize major histocompatibility complex class I (MHC-I) molecules (missing self hypothesis [33]).…”
mentioning
confidence: 99%